Factors influencing the delay in childbearing: A narrative review - Faranak Safdari-Dehcheshmeh; Mahnaz Noroozi; Fariba Taleghani; Soraya Memar (Wolters Kluwer Medknow Publications, 2023)
Background: Delay in parenthood and the related consequences for health, population, society, and economy are significant global challenges. This study was conducted to determine the factors affecting delay in childbearing. Materials and Methods: This narrative review was conducted in February 2022 using databases: PubMed, Scopus, ProQuest, Web of Science, Science Direct, Cochrane, Scientific Information Database, Iranian Medical Articles Database, Iranian Research Institute for Information Science and Technology, Iranian Magazine Database, and Google Scholar search engine. The search terms used included "delayed childbearing," "delayed parenthood," "delayed fertility," "delay of motherhood," "parenthood postponement," "deferred pregnancy," "reproductive behavior," and "fertility." Results: Seventeen articles were selected for final evaluation. The factors were studied at micro and macro levels. The factors in micro level fell into two classes: personal and interpersonal. Personal factors included extension of women's education, participation in the labor market, personality traits, attitude and personal preferences, fertility knowledge, and physical and psychological preparation. The interpersonal factors included stable relations with spouse and other important people. The macro level included supportive policies, medical achievements, and sociocultural and economic factors. Conclusions: Policy-making and enforcement of interventions, such as improvement of the economic conditions, increased social trust, providing adequate social welfare protection, employment, and support of families using such strategies as creating family-friendly laws, taking into consideration the conditions of the country will reduce the insecurity perceived by the spouses and contribute to a better childbearing plan. Also, improving self-efficacy, increasing couples' reproductive knowledge and modifying their attitude can be helpful to better decision-making in childbearing.